The Effect of Family-Based Empowerment Program on the Weight and Length of Hospital Stay of Preterm Infants in the Neonatal Intensive Care Unit: - Beheshtipoor, Noushin; Shaker, Zohreh; Edraki, Mitra; Razavi, Mostajab; Zare, Najaf (Galen Medical Journal, 2013)
Background: Preterm infants need to be hospitalized in the Neonatal Intensive Care Unit (NICU) and receive specific systematic care in order to survive. Nonetheless, long hospital stay leads to parents’ separation from the infant and disturbance in the family life. It also has many undesirable effects on the infant. The present study aimed to determine the effect of family-centered empowerment program on the weight and duration of hospital stay of the infants in NICU. Methods: In this clinical trial, 100 mothers with preterm infants hospitalized in NICU were divided into an intervention and a control groups. The mothers in the empowerment group took part in a multi-stage training program and received the necessary information regarding preterm infants and how to cooperate in taking care of them through face-to-face training, working at the bedside, educational film, and illustrated booklet. Then, the weight of the infants in the two groups and duration of hospital stay were compared. Results: The mean length of hospital stay was 10.5±7.7 and 17.4±11.2 days in the intervention and the control group, respectively, and the results of independent T-test showed that the difference was statistically significant (P=0.001). The mean of weight changes was -42.4±172.9 grams in the control group and -22.6±162.0 grams in the intervention group; no significant difference was found between the two groups (P=0.556). Conclusion: The family-centered empowerment program in the NICU significantly reduced the infants’ length of hospital stay, but had no effects on their weights.